‘SHALL’ AMBIGUITIES IN EU LEGISLATIVE TEXTS - FELICI, Annarita (Comparative Legilinguistics, 2012)
This paper investigates the modal ‘shall’, whose excessive use can be problematic both in legal translation and interpretation (Coode 1843, Driedger 1976). The context of analysis is the EU for offering a relative young legal environment where translation represents the main channel of communication. The analysis moves from the deontic speech acts of ordering and prohibiting and looks at examples of performativity where ‘shall’ is not only deontically binding, but it is also used to express a necessary condition or to set a new state of things up. The disambiguation is particularly evident in multilingual translation and is performed with the help of parallel concordances, which also shed light on the conceptual framework of norms. Data consist of a parallel corpus including English, French, German and Italian versions of EU legislative texts chosen between 2001-04. As a term of comparison, a small comparable corpus containing English orginal texts has also been compiled.